Gender based violence in university communities : policy, prevention and educational initiatives - Anthia, Sundari; Lewis, Ruth (Bristol ; Chicago, IL : Policy Press, 2018)
This book provides the first in-depth overview of research and practice in gender based violence in universities. It sets out the international context of ideologies, politics and institutional structures that underlie responses to gender based violence in Britain and further afield in Europe, in the US, and in Australia, and considers the implications of implementing related policy and practice.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Campus violence -- Great Britain; Women -- Violence against -- Great Britain